PERSPECTIVES OF E-CONTENT: A SYSTEMATIC REVIEW - Dr.iInderpreet Kaur, Ms Jyoti ,Ms.Raskirat (International Journal of Advanced Science and Technology, 2020)
Throughout recent decades, as the issue of social advancement has gone to the fore, the drive to improveaccess to instruction has been behind the development in into e-learning. Technology is the use ofscientific knowledge for the welfare of all. Technology has become an integral part of life these days.Technology has also changed the process of teaching and learning. E-content is the outcome of usage oftechnology in our classrooms. E-content do not tend to replace traditional teaching and learning but areexpected to complement each other. So before proceeding to the development of E-content, it is necessaryto review, all the perspectives of e-content. The current systematic review has brought up the issue of thepresence of studies tending to the particular needs of people. In reality, e-learning is required to be oneof the basic tools for improving access to instruction and at last supporting social incorporation. Thesystematic literature review was performed through a four-step process including an exhaustive search ofscientific literature databases, the selection of studies through exclusion and inclusion criteria, andliterature analysis and synthesis. The main results are 38% studies regarding the development of econtent, 28% studies has analyzed impact of e-learning, and 19% studies carried out on the challengesin the development and implementation of e-content. Finding the gaps of the examinations, no paper hasestimated cognitive load after the usage of e-content, alongside this none of the investigations estimatedhow the reasoning abilities change after the execution of e-content, Which turns out as the hole of theresearch?